Ethical Use of Social Media to Facilitate Qualitative Research. (January 2015) - Lunnay, Belinda; Borlagdan, Joseph; McNaughton, Darlene; Ward, Paul
Increasingly, qualitative health researchers might consider using social media to facilitate communication with participants. Ambiguity surrounding the potential risks intrinsic to social media could hinder ethical conduct and discourage use of this innovative method. We used some core principles of traditional human research ethics, that is, respect, integrity, and beneficence, to design our photo elicitation research that explored the social influences of drinking alcohol among 34 underage women in metropolitan South Australia. Facebook aided our communication with participants, including correspondence ranging from recruitment to feeding back results and sharing research data. This article outlines the ethical issues we encountered when using Facebook to interact with participants and provides guidance to researchers planning to incorporate social media as a tool in their qualitative studies. In particular, we raise the issues of privacy and confidentiality as contemporary risks associated with research using social media.